2012
DOI: 10.1097/ijg.0b013e318207091a
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypotony After Transscleral Diode Cyclophotocoagulation

Abstract: Underlying diagnosis of neovascular glaucoma is a significant risk factor for hypotony post TCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 17 publications
1
81
3
1
Order By: Relevance
“…Ramli et al . in a recently published study investigated the risk factors for hypotony after TSCPC in an Asian population . With a comparatively high hypotony rate of 17.7%, they identified NVG as a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramli et al . in a recently published study investigated the risk factors for hypotony after TSCPC in an Asian population . With a comparatively high hypotony rate of 17.7%, they identified NVG as a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The 27 TSCPC study groups included in the pooled analysis are summarized in Table . The mean pooled pretreatment IOP was 35.02 ± 6.11 (SD) mmHg (range 21–46 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to Ahmed valve implantation in a randomized controlled trial, no significant difference was found in the success rate at 24 months between the diode cyclophotocoagulation (61.18 %) and Ahmed glaucoma valve implantation (59.26 %) in NVG treatment [91]. It is important to note, however, that the underlying diagnosis of NVG poses an increased risk for hypotony after transcleral-cyclophotocoagulation [9497]. Endo-cyclophotocoagulation was also shown to be effective in NVG.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies confirm the IOP-lowering ability of TSCPC [35] ; however, there is conflicting data on the complication rates of this procedure. Ramli et al [12] and Murphy et al [13] both reported that there was a significant risk of developing serious complications such as hypotony, while Osman et al [14] and Ansari and Gandhewar [15] reported no significant risk for development of these complications. This conflicting data, along with many reports of operative and postoperative pain associated with this procedure [16,17] merit consideration on how to maintain good outcomes while lowering complications and pain.…”
Section: Discussionmentioning
confidence: 99%